Analysis The Aspects of Self-Love in a Children's Storybook “Rafa, The Raflesia” - Kasmiati; Wulandari, Suci (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Self-love is an ability to appreciate and love yourself as a noble person with weaknesses and strengths that always accompany it. In today's era, humans often have difficulty in treating themselves well and behaving as they are due to various factors. Self-love seems important to be instilled in children from an early age, one of which is through the media of story books, in order to create a strong personality in the future when he grows up. The purpose of this study is to analyze the aspects of self-love in the story book entitled